Study of the changing trends in place of delivery in rural women in relation to pre and post NRHM period in Paithan, Aurangabad, Maharashtra - Pund, Sandeep B.; Kuril, Bina M.; Doibale, Mohan K.; Ankushe, Rajendra T.; Kumar, Purushottam; Siddiqui, Nafeha (International Journal Of Community Medicine And Public Health, 2017)
Background: Maternal health reflects the overall effectiveness of the health system of any country. One strategy for reducing maternal mortality and morbidity is ensuring that every baby is delivered in an institution. Government of India has launched various health schemes under the umbrella of National Rural Health Mission (NRHM) to promote institutional deliveries. Thus this study was conducted to study the changing trends in place of delivery in rural women in relation to NRHM. Methods: A community based cross-sectional study was conducted in the field practice area of rural health training center (RHTC), Paithan, Dist. Aurangabad during the period of 1st October 2015 to 31st March 2016. All the villages under two sub-centers of one PHC under the RHTC were selected for the study. All women above 18 years of age who delivered at least once between 1st January 2001 to 31st December 2015, were interviewed for their place of delivery. Results: Institutional deliveries increased from 47.06% to 93.65% in 2001 to 2015. The odds for institutional deliveries in the post NRHM period were seen to vary in the 1st 5 years of NRHM and the next 5 years. In 2006-10, odds of institutional deliveries were 2.44 times more, whereas in 2011-15 the odds were 8.99 times more than the pre-NRHM period. The overall odds of institutional delivery in the post-NRHM period were 4.1 times more than the pre-NRHM period. Conclusions: Increasing trends of institutional deliveries and decreasing trends of home deliveries was observed from 2001 to 2015. Increase in deliveries was seen in both government as well as private hospitals. Institutional deliveries have increased rapidly since the implementation of NRHM with 4.1 times more chance of institutional deliveries in the post-NRHM period.